The Urgency of Embodiment of Open Government As an Effort to Realize the Fulfillment of the Social, Political and Economic Rights of the Indonesian Society - Engga Lift Irwanto; Roni Ekha Putera (Department of Public Administration, 2023)
The Open Government Policy is a tool for achieving an increase in the quality of democracy in a country to improve meeting the needs of the people through an open policy governance. This policy generates various benefits for the business world and citizens, including for the government that implements the policy. Then this concept of openness sparked a movement that was followed globally, the emergence of government data portals that continue to spread, created by governments and multilateral independent teams working with governments working to develop open government data in a country. In Indonesia the open government movement has been responded to by the Indonesian government through Open Government Indonesia (OGI) which has been rolling since 2011 both in central government and regional government. The OGI movement was born from a similar movement called the Open Government Partnership. The Open Government Partnership (OGP) is a multilateral initiative that aims to secure government concrete commitments in increasing transparency, empowering people, fighting corruption, and leveraging new technology to strengthen government. OGP was officially founded on 20 September 2011 by eight countries, namely Brazil, Indonesia, Mexico, Norway, the Philippines, South Africa, England and the United States.